Cognitive stimulation therapy in dementia care: exploring the views and experiences of service providers on the barriers and facilitators to implementation in practice using Normalization Process Theory. (13th July 2017) - Dickinson, Claire; Gibson, Grant; Gotts, Zoe; Stobbart, Lynne; Robinson, Louise
ABSTRACT: Background: Cognitive stimulation therapy (CST) is an evidence-based, cost-effective psychosocial intervention for people with dementia but is currently not a standard part of post-diagnostic care. This qualitative study explored the views and experiences of dementia care providers on the barriers and facilitators to its implementation in usual care. Method: Thirty four semi-structured interviews (24 participants) were conducted across four dementia care sites in the North of England; ten were follow-up interviews. Data were analyzed using thematic analysis and then mapped to the Normalization Process Theory framework. Results: Participants considered CST a "good fit" with their "preferred" ways of working and goals of dementia care namely the provision of person-centered services. For facilitators delivering the intervention, compared to other behavioral interventions, CST was seen to offer benefits to their work and was easy to understand as an intervention. Training in CST and seeing benefits for clients were important motivators. Time and resources were crucial for the successful implementation of CST. Participants were keen to objectively measure benefits to participants but unsure how to do this. Conclusions: CST is a cost-effective psychosocial intervention for people with dementia, recommended by national guidance. Despite our findings which show that, using the NPT framework, there are more facilitators than barriers to the implementation of CST, it is still not a standard part of post-diagnostic dementia care. Further research is needed to explore the reasons for this implementation gap in ensuring evidence-based care in translated into practice.